2015
DOI: 10.1371/journal.pone.0135766
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes and Prognostic Factors of Trabeculectomy following Intraocular Bevacizumab Injection for Neovascular Glaucoma

Abstract: PurposeTo evaluate long-term outcomes and identify prognostic factors of trabeculectomy following intraocular bevacizumab injection for neovascular glaucoma.MethodsSixty-one eyes of 54 patients with neovascular glaucoma treated by trabeculectomy following intraocular bevacizumab injection were consecutively enrolled. Surgical success criteria were sufficient intraocular pressure (IOP) reduction (IOP ≤21 mmHg, ≥20% IOP reduction, no additional medications or glaucoma surgeries) without devastating complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Similar results have also been demonstrated in other studies showing unchanged final VA in patients with initial poor VA (counting fingers and light perception). 17,19 In contrast, another study reported better results in eyes with early NVI. 15,20 From this study, on management patient with DM and NVG eyes in the Indonesian population: the first step in the controlling of NVG is to reduce IOP as quickly as possible in order to minimize optic nerve damage caused by a high IOP.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Similar results have also been demonstrated in other studies showing unchanged final VA in patients with initial poor VA (counting fingers and light perception). 17,19 In contrast, another study reported better results in eyes with early NVI. 15,20 From this study, on management patient with DM and NVG eyes in the Indonesian population: the first step in the controlling of NVG is to reduce IOP as quickly as possible in order to minimize optic nerve damage caused by a high IOP.…”
Section: Discussionmentioning
confidence: 94%
“…Damage to these vessels can lead to intraoperative bleeding. 7,13,19 Therefore, the use of fast-acting anti-VEGF agents is rationalized prior to such surgery in order to reduce and induce anterior segment neovascularization regression. 20,21 Anti-VEGF induce regression of neovascularization in PDR and also facilitate rapid regression of anterior segment neovascularization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The definition of NVG was: (1) IOP>21 mmHg; (2) caused by retinal vascular disease (RVO or DR); (3) the presence of active neovascularization in the iris and/or angle; (4) with or without antiglaucomatous medications. [23] Newly diagnosed NVG patients and referral NVG patients were also included. Each patient underwent a standardized ophthalmic examination, which included refractive status, slit-lamp biomicroscopy, fundus examination, IOP (intraocular pressure), CCT (central corneal thickness), AL (axial length), ACD (anterior chamber depth), visual field examination, and gonioscopy, performed by glaucoma specialists.…”
Section: Methodsmentioning
confidence: 99%